PENGARUH PENGETAHUAN DAN MOTIVASI KERJA KADER POSYANDUTERHADAP KUALITAS PELAYANAN KESEHATAN BALITA DAN IBU HAMIL DI POSYANDU DESA TEMON KECAMATAN BATURETNO WONOGIRI - Ikhwan Zaeni; Fajar Alam Putra; Farida Nugrahani (Jurnal Ilmu Keperawatan Indonesia (JIKI), 2015)
Background: Posyandu program implemented for the benefit of society, it is expected that the community itself is the active form, organize, exploit and develop best IHC. Continuity IHC depends on the participation of the community itself. The organizers of IHC are cadres and the PKK from the village (Budioro, 2002). Based on the above description, it can be formulated: "Is there an effect of the level of Knowledge and Work Motivation Cadre IHC on the Quality of Health Care Toddler And Pregnant Women In Rural IHC TemonKecamatan Baturetno Winton?" Methodology: The research design used was a descriptive cross sectional correlation (cross-sectional). The population in the village cadres IHC Baturetno Temon District of Winton, a sample of 30 respondents. Analysis of the data by Linear. Results: Based on the results of the regression analysis and t test note that amounted to 4,594 tcount the value ρ = 0.000